Зарождение нанокристаллов Al в аморфном сплаве Al₈₇Ni₈Y₅при нагреве с постоянной скоростью - Рассолов, С.Г.; Ткач, В.И.; Максимов, В.В.; Коваленко, О.В.; Моисеева, Т.Н.; Попов, В.В. (Физика и техника высоких давлений, 2013)
Методами рентгенографического анализа, резистометрии и измерения микротвердости исследован процесс формирования нанокомпозитной структуры в аморфном сплаве Al₈₇Ni₈Y₅при нагреве со скоростью 5 K/min. Из сопоставления экспериментально измеренных изменений среднего размера нанокристаллов и их объемной доли установлено, что при повышении температуры нагрева скорость зарождения нанокристаллов Al изменяется по кривой с максимумом. Показано, что наблюдаемые изменения скорости зарождения могут быть удовлетворительно описаны в рамках классической модели гомогенного зарождения с учетом снижения термодинамической движущей силы превращения, обусловленного обогащением остаточной аморфной матрицы легирующими элементами. Установлено, что инициация процесса зарождения в ходе предварительного нагрева приводит к увеличению (на ~ 9.5%) микротвердости образцов с нанокомпозитной структурой. За методами рентгенографічного аналізу, резистометрії та вимірювання мікротвердості досліджено процес формування нанокомпозитної структури в аморфному сплаві Al₈₇Ni₈Y₅при нагріванні зі швидкістю 5 K/min. Із зіставлення експериментально виміряних змін середнього розміру нанокристалів і їхньої об’ємної частки встановлено, що при підвищенні температури нагрівання швидкість зародження нанокристалів Al змінюється по кривій з максимумом. Показано, що зміни швидкості зародження, які спостерігаються, можуть бути задовільно описані в рамках класичної моделі гомогенного зародження з урахуванням зниження термодинамічної рушійної сили перетворення, що обумовлено збагаченням залишкової аморфної матриці легуючими елементами. Встановлено, що ініціація процесу зародження в процесі попереднього нагріву призводить до збільшення (на ~ 9.5%) мікротвердості зразків з нанокомпозитною структурою. The process of formation of a nanocomposite structure in the amorphous Al₈₇Ni₈Y₅ alloy at constant heating rate of 5 K/min was studied by X-ray diffraction and measurements of electrical resistance and microhardness changes. By comparison of the experimentally measured changes of the average sizes of nanocrystals and their volume fraction, it was established that the nucleation rate of Al nanocrystals increased with temperature up to about 1.6·10²² m⁻³·s⁻¹ in the range of 488–491 K and then decreased by about an order of magnitude at the final stage of nanocrystallization (570 K). It was shown that the observed behavior of the nucleation rate can be satisfactory described within the classical model of homogeneous nucleation accounting lowering of the thermodynamic driving force of transformation due to the enrichment of the residual amorphous matrix with the alloying elements. It was found that preliminary heating of the samples up to temperatures corresponding to the nucleation rate maximum resulted in lowering of the onset crystallization temperature by about 9 K and enhancement of microhardness of the nanocomposite structure from 5210 to 5700 MPa that was caused by increment of the volume density of Al nanocrystals from 1.87·10²³ to 2.14·10²³ m⁻³.